2010
DOI: 10.1103/physrevc.81.024909
|View full text |Cite
|
Sign up to set email alerts
|

Systematic theoretical uncertainties in jet quenching due to gluon kinematics

Abstract: We find that the current radiative energy loss kernels obtained from the opacity expansion dramatically violate the collinear approximation used in their derivation. By keeping only the lowest order in collinearity terms, models based on the opacity expansion have ∼50% systematic uncertainty in the calculation of π 0 R AA in the most central RHIC collisions, resulting in a systematic uncertainty of ∼200% in the extracted medium density. Surprisingly, the inclusion of a thermal gluon mass of the order of the De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…III B, for the opacity expansions, where the resulting uncertainty is found to be about a factor 2 in the gluon spectra. The resulting uncertainty in R AA decreases with increasing p T [54]. In Sec.…”
Section: Summary Of the Main Findingsmentioning
confidence: 83%
See 2 more Smart Citations
“…III B, for the opacity expansions, where the resulting uncertainty is found to be about a factor 2 in the gluon spectra. The resulting uncertainty in R AA decreases with increasing p T [54]. In Sec.…”
Section: Summary Of the Main Findingsmentioning
confidence: 83%
“…6). However, owing to nontrivial interference effects, its effect on observables such as R AA is actually not very large [54].…”
Section: Single Emission Kernelmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, non-perturbative approaches, for example those based on AdS/CFT gauge gravity duality [1], seem to work well. Even within the pQCD framework, there are many models that are based on different and often uncontrolled approximations [2], which, when tuned to the same data, predict very different medium properties.…”
Section: Introductionmentioning
confidence: 99%
“…For energy loss, this distribution is integrated over k t and the behavior at large angles is linked to how the kinematic constraints on the parton are enforced and the assumption of collinearity. It has been shown that the choice of maximum opening angle θ max can change the results appreciably, leading to at the least a large systematic error [150,178] Clearly the assumption of collinearity is badly violated: for values of x ⇠ µ/E, dN g /dxdk T reaches its maximum value at k T ⇠ xE. For these values of x the emission spectrum is highly sensitive to the choice of k max :…”
mentioning
confidence: 99%